PIDANA TERHADAP PENGENDARA SEPEDA MOTOR BAGI ANAK-ANAK DI BAWAH UMUR DAN MELAKUKAN PELANGGARAN LALU LINTAS - Syaputra, Pratama; Fuah, Mar (Desiderata Law Review, 2024)
This research discusses legal handling of minors who ride motorbikes without permission and commit traffic violations. This phenomenon is a serious problem because children who do not yet have a driving license (SIM) are often involved in traffic accidents, which not only cause material losses but also result in loss of life. Legal handling of children refers to the Juvenile Criminal Justice System Law (UU SPPA) which applies a diversion and restorative justice approach to protect children's rights. Legal procedures are specifically designed to minimize negative impacts on children through investigations, prosecutions and trials with special treatment. Apart from that, parental parenting and legal indiscipline are the main causes of this violation. The results of the research show that sanctions against children can be in the form of light crimes or coaching actions that take into account the best interests of the child, with the role of parents and society as important elements in preventing violations.